The role and limitations of technology in U.S. counterinsurgency warfare - Rubright, Richard W. 1974- (Potomac Books, An imprint of the University of Nebraska Press, 2015)
Although the United States plays a leading role in the development of technology, particularly that used by militaries around the world, the U.S. military nonetheless continues to find itself struggling against lower-tech foes that conduct warfare on a different scale.